Calendário de Sazonalidade de Hortifrutícolas Não Convencionais ou Negligenciadas - Marianna Esteves dos Santos; Márcio Marques Silva; Avany Fernandes Pereira; Thadia Turon Costa da Silva (Universidade do Estado do Rio de Janeiro, 2021)
Introduction: With a huge variety of edible plants, native or exotic, Brazil's  biodiversity is underexploited as far as food is concerned. Objective: To develop a Seasonality Calendar to promote further knowledge, use and preservation of these species that make up Brazil's biodiversity. Methods: Systematization of information about the harvest period of unconventional or neglected horticultural products, through a review of the scientific literature, by classifying them according to the parts used in human nutrition, such as fruits, fruit-vegetables, herbaceous vegetables and seeds. Results: The calendar includes 71 species, classified into 60 native and 11 exotic ones, subdivided into 59 fruits, 3 fruit-vegetables, 13 herbaceous vegetables and 6 seeds. Conclusions: There need to be more studies focused on this topic owing to its relevance and scarcity of works that present easily applicable tools to encourage the use of unconventional or neglected horticultural crops in cuisine and gastronomy. Therefore, the population and, especially, culinary professionals (when planning menus) are expected to use this knowledge with a view to valuing food culture and the conservation of Brazilian biodiversity.